2009
DOI: 10.1038/leu.2009.131
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the hTERT promoter by the proto-oncogenic protein TAL1

Abstract: Telomerase activity, which has fundamental roles in development and carcinogenesis, strongly depends on the expression of human telomerase reverse transcriptase (hTERT), its catalytic subunit. In this report, we show that the basic helix-loophelix factor, TAL1 (T-cell acute lymphoblastic leukemia 1), is a negative regulator of the hTERT promoter. Indeed, TAL1 overexpression leads to a decrease in hTERT mRNA abundance and hence to reduced telomerase activity. Conversely, suppression of TAL1 by RNA interference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(52 reference statements)
0
9
0
1
Order By: Relevance
“…HBZ has been reported to promote human TERT (hTERT) expression via enhancing its promoter activity in association with JunD [ 68 ]. The activities of two inhibitors of the hTERT promoter, TAL1 and menin, are also suppressed by HBZ [ 69 , 70 ]. Elevation of hTERT levels by HBZ may allow sustained proliferation of ATL cells, which have been reported to overexpress hTERT [ 71 , 72 ].…”
Section: Reviewmentioning
confidence: 99%
“…HBZ has been reported to promote human TERT (hTERT) expression via enhancing its promoter activity in association with JunD [ 68 ]. The activities of two inhibitors of the hTERT promoter, TAL1 and menin, are also suppressed by HBZ [ 69 , 70 ]. Elevation of hTERT levels by HBZ may allow sustained proliferation of ATL cells, which have been reported to overexpress hTERT [ 71 , 72 ].…”
Section: Reviewmentioning
confidence: 99%
“…4 C, lanes 3 and 4). We previously reported that TAL1 was able to negatively regulate the promoter of the protein subunit of the telomerase enzyme [25] . By testing the effect of SMAD3 on the hTERT promoter we also observed a dose dependent negative effect ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids used in this study have been previously described: pSGF-TAL1 [24] , pSG5-MYC-TAL1 [25] and pSG-HA-Ub [26] . pCMV-Flag-E47 was kindly provided by C. Gallego [27] .…”
Section: Methodsmentioning
confidence: 99%
“…L'expression d'HBZ augmente en particulier l'activité transcriptionnelle de JunD sur le gène hTERT, codant la sous-unité catalytique de la télomérase. HBZ induit par ailleurs la dégradation par le protéasome de TAL1 (T-cell acute lymphoblastic leukemia 1), un régulateur négatif du promoteur de hTERT [32]. Ces résultats indiquent que l'activité télomérase élevée observée chez les patients souffrant d'ATLL est, en partie du moins, la conséquence de ces rôles convergents d'HBZ [18].…”
Section: Réplicationunclassified